From biometric data to cryptographic primitives: A new method for generation of substitution boxes - Özkaynak, Fatih (Association for Computing Machinery, 2017)
Rapid developments in information and communication technologies have greatly digitization of our daily lives. One of the biggest threats to our digital existence is how to ensure information security. Solutions based on biometric data have become more widespread in recent years to provide information security. In this study, a method is proposed to show how biometric data can be used in the design of cryptographic primitives. Substitution boxes are an important cryptographic primitive in the designing of block cipher. There are many different methods for generation of substitution boxes. Random selection is one of these methods. In this study, biometric data have been used as selection method for determining of randomness sources. Biometric data will be a good source of randomness since they are person-specific. The experimental analyses showed that successful results have been obtained for the five most widely used evaluation criteria of substitution boxes. © 2017 Association for Computing Machinery.
2017 International Conference on Biomedical Engineering and Bioinformatics, ICBEB 2017 -- 14 September 2017 through 16 September 2017 -- Bangkok -- 131935
Keywords: Chaos; Cryptography; Information security; Iris; Security applications of biometric data; Substitution box